Occupying multiple stigmatized identities: Smoking and unemployment stigmas among the unemployed - Priya Fielding-Singh; Erin A. Vogel; Judith J. Prochaska (Elsevier, 2020)
Stigma - which involves stereotyping, discrimination, and status loss - is a central driver of morbidity and mortality. Given the de-normalization of smoking and the status loss of unemployment, unemployed individuals who smoke may occupy multiple stigmatized identities. As such, this study examined aspects and correlates of smoking and unemployment stigmas among unemployed job-seekers who smoke. Adult job-seekers who smoke tobacco (N = 360) were recruited at government-run employment development departments (EDDs) in the San Francisco Bay Area in 2015-2018. Participants completed measures of smoking and unemployment stigma and self-reported their demographic, tobacco use, and physical and mental health characteristics. Smoking and unemployment stigmas were moderately positively correlated, and the sample reported higher unemployment stigma than smoking stigma. A sample majority endorsed at least one element of smoking and unemployment stigmas; most common for both was self-disappointment. Two sets of linear regression analyses using a general-to-specific modeling procedure were run to identify significant correlates of smoking stigma and unemployment stigma. Both stigmas were significantly associated with depressive symptoms and with preparing to quit smoking. Participants in poorer health and those with stable housing endorsed greater smoking stigma, while unemployment stigma was endorsed more among White individuals and those with past-year e-cigarette use. The findings highlight the need to examine multiply occupied stigmas as a social determinant of population health.